(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Three consequences based on the basic law of the flat interlocking have been determined that allow the generation of asymmetric tooth profile on different poloidal circles. Gears with asymmetric profile are used in both mechanical engineering and measuring devices. Qualitative indicators of engagement that cannot be accomplished with a symmetric profile have been developed. A specific example of generation III has been presented. The qualitative indicators of engagement, which are invariant to the parameters of the tool, have been improved.